The Marketing Practices in the Level of Customers Satisfaction in Printing Shop: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study is conducted to determine the impact of marketing practices on customer satisfaction at Seal Barcode. The researchers developed this study to determine the impact of marketing practices on customer satisfaction. It also seeks to identify what marketing practices Seal Barcode needs to maintain and what needs to improve. This study utilised a descriptive research method of design that involves collecting and analyzing data. This study utilised a convenience sampling technique to select participants. The researchers described the respondent group using descriptive statistics. Based on the results, about half were 16-21 years old or 22-27 years old. The majority of the females were unemployed. Discounts, price affordability, and combining online and offline customers were assessed variables. Regarding customer satisfaction with the services, variables such as printing quality and customer service both get a very high rate and business schedules to get highly satisfied. The researchers recommend that the seal barcode improve its services, particularly customer assistance, to avoid the potential consequences of a lack of customer care, as well as service improvements and advice enhancing and developing print quality, as well as maintaining and improving their positive relationships with customers and company schedules. The researchers also recommend that customers who print a lot be given a discount and that clients be given a member card or loyalty card. They suggest that Seal Barcode increase their print quality and upgrade their customers.
Keywords: marketing practices; customer satisfaction; printing shop